Postoperative neoadjuvant temozolomide before radiotherapy versus standard radiotherapy in patients 60 years or younger with anaplastic astrocytoma or glioblastoma: a randomized trial. (2nd December 2017) - Malmström, Annika; Poulsen, Hans Skovgaard; Grønberg, Bjørn Henning; Stragliotto, Giuseppe; Hansen, Steinbjørn; Asklund, Thomas; Holmlund, Birgitta; Łysiak, Małgorzata; Dowsett, Joseph; Kristensen, Bjarne Winther; Söderkvist, Peter; Rosell, Johan; et al.
Abstract: Introduction: A pilot study of temozolomide (TMZ) given before radiotherapy (RT) for anaplastic astrocytoma (AA) and glioblastoma (GBM) resulted in prolonged survival compared to historical controls receiving RT alone. We therefore investigated neoadjuvant TMZ (NeoTMZ) in a randomized trial. During enrollment, concomitant and adjuvant radio-chemotherapy with TMZ became standard treatment. The trial was amended to include concurrent TMZ. Patients and methods: Patients, after surgery for GBM or AA, age ≤60 years and performance status (PS) 0–2, were randomized to either 2–3 cycles of TMZ, 200 mg/m 2 days 1–5 every 28 days, followed by RT 60 Gy in 30 fractions or RT only. Patients without progressive disease after two TMZ cycles, received the third cycle. From March 2005, TMZ 75 mg/m 2 was administered daily concomitant with RT. TMZ was recommended first-line treatment at progression. Primary endpoint was overall survival and secondary safety. Results: The study closed prematurely after enrolling 144 patients, 103 with GBM and 41 with AA. Median age was 53 years (range 24–60) and 89 (62%) were male. PS was 0–1 for 133 (92%) patients, 53 (37%) had complete surgical resection and 18 (12%) biopsy. Ninety-two (64%) received TMZ concomitant with RT. Seventy-two (50%) were randomized to neoadjuvant treatment. For the overall study population survival was 20.3 months for RT and 17.7 months for NeoTMZ ( p = .76), this not reaching the primary objective. For the preplanned subgroup analysis, we found that NeoTMZ AA patients had a median survival of 95.1 months compared to 35.2 months for RT ( p = .022). For patients with GBM, no difference in survival was observed ( p = .10). MGMT and IDH status affected outcome. Conclusions: No advantage of NeoTMZ was noted for the overall study population or subgroup of GBM, while NeoTMZ resulted in 5 years longer median survival for patients diagnosed as AA.